-5(k-8)+7(-5+k)=-3

Simple and best practice solution for -5(k-8)+7(-5+k)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(k-8)+7(-5+k)=-3 equation:


Simplifying
-5(k + -8) + 7(-5 + k) = -3

Reorder the terms:
-5(-8 + k) + 7(-5 + k) = -3
(-8 * -5 + k * -5) + 7(-5 + k) = -3
(40 + -5k) + 7(-5 + k) = -3
40 + -5k + (-5 * 7 + k * 7) = -3
40 + -5k + (-35 + 7k) = -3

Reorder the terms:
40 + -35 + -5k + 7k = -3

Combine like terms: 40 + -35 = 5
5 + -5k + 7k = -3

Combine like terms: -5k + 7k = 2k
5 + 2k = -3

Solving
5 + 2k = -3

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 2k = -3 + -5

Combine like terms: 5 + -5 = 0
0 + 2k = -3 + -5
2k = -3 + -5

Combine like terms: -3 + -5 = -8
2k = -8

Divide each side by '2'.
k = -4

Simplifying
k = -4

See similar equations:

| 2x+10+3x=55 | | 2(u+8)=-6(3u-1)+8u | | 5(4v-5)=5v+4 | | 36=-9(-5+1) | | 8g-3(5+2g)=85-3g | | (3x-4)(7x+5)=0 | | 4y+10=180 | | x+32=3x+24 | | -3(8-7n-2)=18 | | 12f-15=12f-15 | | 14+8m=14-3m-5 | | 16m+4x=y | | 10x^2-36x+27=0 | | 3x-2x-4=17 | | 2(x-5)-(3x+6)=-13 | | In(3x)+In(2x)=3 | | 3(5x+4)+12=-8 | | V=pir | | 20y=13000 | | 10-3s=s | | 2(x-5)-(3x+6)=-12 | | -1=-6x+5x+5 | | 4x-2x+4=24 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=f(x) | | -1=-6x | | 3x+-7=8+6(x+2) | | 8n-1(2n-3)= | | -5n-7=3n+41 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=0 | | 4p=63 | | 4(y-1)=4 | | 12=0.25(R) |

Equations solver categories